Seasonality of reproduction in ungulates : the effect of photoperiod on reproduction in a seasonal breeder, the sheep (Ovis aries) and a putative aseasonal breeder, the springbok (Antidorcas marsupialis) - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1998.